Relationship between body composition parameters and metabolic syndrome in young Thai adults - Namwongprom,S. (Galenos Yayincilik, 2015)
© Journal of Clinical Research in Pediatric Endocrinology. Objective: The aim of this study was to evaluate the relationship between body composition parameters, i.e. waist circumference, android fat mass (AFM), gynoid fat mass (GFM), android to gynoid fat mass ratio (AG ratio) and metabolic syndrome (MS) risk components in young Thai adults. Methods: This was a cross-sectional study conducted among 391 adolescents (174 male, 217 female). The body mass index (BMI), waist circumference, blood pressure, triglyceride, high-density lipoprotein (HDL) cholesterol and glucose levels were determined. AFM, GFM and AG ratio were assessed by dual-energy X-ray absorptiometry (DXA). Linear regression analysis was done to assess the relationship of waist circumference, AFM, GFM and AG ratio with MS risk components’ score, separately. Results: Among 391 young adults aged 18.5-21.8 years, MS was found in 5.9%. Participants with MS (n=23) had a significantly higher weight, height and BMI than those without MS. There was no statistically significant difference in bone mineral density between the two groups. At univariable linear regression analysis, waist circumferences, AFM, GFM and AG ratio showed significant relationship with MS risk components’ score. However, after adjusting for gender, birth weight and BMI, AG ratio demonstrated greater relationship with MS risk components’ score (β 1.89, 95%CI 1.096- 2.978) than waist circumference (β 0.046, 95%CI 0.033-0.058) and AFM (β 0.979, 95%CI 0.667-1.290). No significant association was observed between GFM and MS risk components’ score (β 0.077, 95%CI -0.089-0.243). Conclusion: The results from this study indicated that AG ratio is a stronger predictor of MS than waist circumference and AFM in young Thai adults. The role of AG ratio for the diagnosis of MS needs to be further investigated.